Low-dose β-carotene Supplementation and Deworming Improve Serum Vitamin A and β-carotene Concentrations in Preschool Children of Bangladesh (Journal of Health, Population and Nutrition, 2010)
Despite the national vitamin A and antihelminthic prophylaxis programmes, both intestinal geohelminthsand subclinical vitamin A deficiency continue to be prevalent among children in developingcountries. Studies on potential synergistic effects of vitamin A supplementation and deworming on retinolstatus have inconsistent results. The purpose of the present study was to investigate the impacts of low-doseβ-carotene supplementation and antihelminthic therapy on serum retinol and β-carotene concentrationsin preschool children of Bangladesh. Two hundred and forty-four children, known to be infected with Ascarislumbricoides, were randomized into four treatment groups: I-IV. Group I and II received two oral dosesof 400 mg of albendazole each, the first dose at baseline and the second dose after four months; Group IIIand IV received placebo in place of albendazole. In addition, Group I and III received 1.2 mg of β-carotenepowder in capsule daily for six months, and Group II and IV received placebo in place of β-carotene. Serumretinol and β-carotene levels were measured before and after six months of the interventions. Serumretinol and β-carotene increased significantly in Group I where both antihelminthic therapy and dailyβ-carotene supplementation were given (p